Social networks and household food consumption smoothing in the presence of idiosyncratic shocks: insights from rural Kenya. Issue 3 (2nd April 2020) - Mbugua, Mercy; Nzuma, Jonathan; Muange, Elijah; Kunyanga, Catherine
ABSTRACT: Idiosyncratic shocks are among the major shocks affecting smallholder households. Social networks have been widely used by households as an informal strategy to smooth consumption. This article uses panel data from 719 smallholder farmers in Kenya and a fixed effects panel data regression model to evaluate the effect of social networks on food consumption smoothing in the presence of health shocks. Fixed effects estimates show that financial credit networks have a positive and significant effect on insurance of purchased food consumption against health shocks, indicating that the networks play an insurance role against health shocks.